2016
DOI: 10.3892/ijmm.2016.2782
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid shifts rosiglitazone-induced adipogenic differentiation to osteogenic differentiation in mouse embryonic fibroblasts

Abstract: Rosiglitazone (RSG) is a potent drug used in the treatment of insulin resistance; however, it is associated with marked skeletal toxicity. RSG-induced osteoporosis may contribute to the promotion of adipogenic differentiation at the expense of osteogenic differentiation in bone marrow stromal cells. The aim of this study was to investigate whether RSG-induced bone toxicity can be reversed by combined treatment with all-trans retinoic acid (ATRA). We examined different osteogenic markers in mouse embryonic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…By contrast, RSPO2 decreased BMP signaling activity induced by BMP4 or siRSPO2 (Figures S1I-S1K). In addition, we stimulated THP-1 cells with all-trans-retinoic acid (ATRA), which regulates BMP signaling in multiple contexts (Cruz et al, 2019;Shao et al, 2016). ATRA administration induced Smad1-phosphorylation and…”
Section: Rspo2 Antagonizes Bmp Signaling In Aml Cellsmentioning
confidence: 99%
“…By contrast, RSPO2 decreased BMP signaling activity induced by BMP4 or siRSPO2 (Figures S1I-S1K). In addition, we stimulated THP-1 cells with all-trans-retinoic acid (ATRA), which regulates BMP signaling in multiple contexts (Cruz et al, 2019;Shao et al, 2016). ATRA administration induced Smad1-phosphorylation and…”
Section: Rspo2 Antagonizes Bmp Signaling In Aml Cellsmentioning
confidence: 99%
“…Correspondingly, retinoic acid has been shown to induce the osteogenic differentiation of stromal cells from both visceral and subcutaneous adipose tissue depots (178). Moreover, as previously demonstrated, in mouse embryonic fibroblasts, 0.4 µM ATRA promotes a shift to osteogenesis from rosiglitazone-induced adipogenic differentiation through the upregulation of Smad1/5/8 phosphorylation and Smad6 expression, resulting in the activation of BMP/Smad pathway (179). At the same time, it has also been observed that pharmacological concentrations of 1-10 µM ATRA inhibit osteoblast proliferation, while increasing its differentiation (180).…”
Section: Vitamin Amentioning
confidence: 68%
“…Nano-Glo Dual-Luciferase Reporter Assay. The iMEFs were seeded in Corning 24-well cell culture plates and transfected with 1 μg firefly luciferase vector, 1 μg Renilla luciferase vector, and 0.5 μg BMP9 binding element luciferase reporter (p12Xsbe-Luc) or Runx2 reporter plasmid (p6Xose2-Luc) per flask using Lipofectamine 2000 [22,23]. Twenty-four hours after transfection, the cells were reseeded in 24-well plates and treated with DMSO, HIF1α, and/or Runx2.…”
Section: Gene Expression Of Osteogenesis-andmentioning
confidence: 99%